ANALISIS PERBANDINGAN DAYA OUTPUT LISTRIK ANTARA PENGGUNAAN TRANSMISI GEAR DAN PULLEY PADA PROTOTYPE (PLTPH) MENGGUNAKAN TURBIN TURGO - Abdi Nugraha, I. M. Tata; Arta Wijaya, I.W.; Budiastra, I.N. (Jurnal SPEKTRUM; Vol 10 No 4 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i04.p1, 2023)
Picohydro Power Plant is one of the environmentally friendly generators that can meet the electricity needs in the vicinity, one of which is in the Kanto Lampo Waterfall Tourism area. The planning of this PLTPH prototype is carried out to meet the lighting needs in the waterfall area. This PLTPH prototype plan uses a turgo turbine and there are two transmissions that can be used, namely, gear and pulley. This study will make a comparison between gear and pulley transmissions with the direct measurement method on the prototype and aims to determine the transmission that can get the best results on the PLTPH prototype. The ratio variations used on gears and pulleys are 4:1, 4:1.3 and 4:2. The PLTPH prototype using a turgo turbine obtained the highest results at a gear ratio of 4:1 with an output power of 48.70 Watt and the resulting torque of 0.613 Nm, while the lowest results were obtained at a pulley ratio of 4:2 with an output power of 10.83 Watt and the resulting torque is 0.147 Nm.